Gestión presupuestaria del GAD de Montalvo del periodo 2020 - 2021. - Gómez Carriel, Diana Roxana (2022)
The Decentralized Autonomous Government of Montalvo Canton is a public institution, with administrative and financial autonomy, aimed at managing the sustainable development of its communities, through its plans and projects established in the annual budget. The objective of this case study is that the citizens of Montalvinos know the final destination of the resources assigned by the Central Government, for this, the descriptive and the documentary investigation method was implemented, where the level of efficiency and effectiveness in the management of its resources, for the fiscal period 2020 - 2021, in which it was possible to detect that there are inconveniences in the public contracting processes, specifically in the purchases that are made and in the contracts for works services.